2019
DOI: 10.1680/jgeot.17.p.091
|View full text |Cite
|
Sign up to set email alerts
|

Greenfield tunnelling in sands: the effects of soil density and relative depth

Abstract: Tunnel construction is vital for the development of urban infrastructure systems throughout the world. An understanding of tunnelling-induced displacements is needed to evaluate the impact of tunnel construction on existing structures. Recent research has provided insight into the complex mechanisms that control tunnelling-induced ground movements in sands; however, the combined influence of relative tunnel depth and soil density has not been described. This paper presents data from a series of 15 plane-strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(13 citation statements)
references
References 26 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…To investigate settlement trough shape characteristics, modified Gaussian curves (Vorster et al, 2005) were fitted to the settlement data using the approach of Marshall et al (2012). Marshall et al (2012) indicated that the conventional Gaussian curve does not always provide a good fit to settlement data for tunnels in sand, which was substantiated by several other studies (Vorster et al, 2005;Marshall et al, 2012;Zhou et al, 2014;Franza and Marshall, 2018;Franza et al, 2019a). The goodness of fit (based on the coefficient of determination R 2 ) of the modified Gaussian curve to vertical displacements is shown in Figure S1 of the supplemental data.…”
Section: Effect Of Model Tunnel On Settlement Trough Shape Characteristicsmentioning
confidence: 89%
See 2 more Smart Citations
“…To investigate settlement trough shape characteristics, modified Gaussian curves (Vorster et al, 2005) were fitted to the settlement data using the approach of Marshall et al (2012). Marshall et al (2012) indicated that the conventional Gaussian curve does not always provide a good fit to settlement data for tunnels in sand, which was substantiated by several other studies (Vorster et al, 2005;Marshall et al, 2012;Zhou et al, 2014;Franza and Marshall, 2018;Franza et al, 2019a). The goodness of fit (based on the coefficient of determination R 2 ) of the modified Gaussian curve to vertical displacements is shown in Figure S1 of the supplemental data.…”
Section: Effect Of Model Tunnel On Settlement Trough Shape Characteristicsmentioning
confidence: 89%
“…This over-prediction is mainly due to the fact that the numerical analyses were not able to accurately replicate the localised zone of vertical settlement close to the tunnel crown, with tunnel boundary displacements therefore propagating through the soil towards the surface more in the numerical analyses than in the centrifuge tests. As suggested by Franza et al (2019a), for dense sand, the arching mechanism has an influential impact, and the soil tends to dilate below the developed arch. However, in the numerical simulations, soil dilation was not accurately replicated, which affected the ability of the numerical models to replicate soil displacements.…”
Section: Settlement Troughsmentioning
confidence: 92%
See 1 more Smart Citation
“…Centrifuge testing has been widely accepted as a tool to investigate pile shaft shearing mechanisms (Bruno, 1999;Nicola and Randolph, 1999;Klotz and Coop, 2001; White and Lehane, 2004). In recent years, tunnel-pile-structure-interaction (TPSI) problems have been investigated using geotechnical centrifuge testing (Loganathan et al, 2000;Jacobsz, 2003;Lee and Chiang, 2007;Marshall and Mair, 2011;Franza et al, 2019). In these centrifuge tests, individual piles or a group of piles connected to a rigid pile cap have been used to investigate tunnel-pile interaction mechanisms during tunnelling, neglecting the effect of a connected structure, which may impact the load transfer between piles during tunnel volume loss, therefore changing an individual pile's resistance or load distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Most of tunneling analysis(Franza et al, 2018, Pescara et al, 2011, Franza and Marshall 2015 has been carried out based on plain strain consideration which has not included longitudinal settlement profile of tunnel. A few researches have been expressed in longitudinal settlement above a tunnel based on field observations Attewell and Woodman (1982).…”
mentioning
confidence: 99%